Electrodeposition of CuInSe2 and In2Se3 on flat and nanoporous TiO2 substrates - Valdes, Matias Hernan (2008)
In2Se3 and CuInSe2 films have been prepared by potentiostatic electrodeposition from deareated aqueous solutions. The substrate consisted of a duplex layer of dense and nanoporous TiO2 obtained by spray pyrolysis deposition (SPD) and doctor blading. In2Se3 thin films are electrodeposited in between the TiO2/CuInSe2 pn heterojunction to block the electron back flow and lower the interfacial recombination produced upon illumination. The films have been characterized using X-ray diffraction, Raman spectroscopy, scanning electron microscopy, and optical transmission. Annealing the samples in Se atmosphere is essential to improve the crystallinity of the In2Se3 and CuInSe2 films. The combination of TiO2/In2Se3/CuInSe2 shows very good diode behavior with a rectification ratio higher than 100 at ±1 V.